Antarctic temperature variability and change from station data. (20th November 2019) - Turner, John; Marshall, Gareth J.; Clem, Kyle; Colwell, Steve; Phillips, Tony; Lu, Hua
Abstract: Variability and change in near‐surface air temperature at 17 Antarctic stations is examined using data from the SCAR READER database. We consider the relationships between temperature, and atmospheric circulation, sea ice concentration and forcing by the tropical oceans. All 17 stations have their largest inter‐annual temperature variability during the winter and the annual mean temperature anomalies are dominated by winter temperatures. The large inter‐annual temperature variability on the western Antarctic Peninsula has decreased over the instrumental period as sea ice has declined. Variability in the phase of the SAM exerts the greatest control of temperatures, although tropical Pacific forcing has also played a large part, along with local atmospheric circulation variability at some locations. The relationship of positive (negative) SAM and high (low) Peninsula and low (high) East Antarctic temperatures was not present before the mid‐1970s. Thirteen of the 17 stations have experienced a positive trend in their annual mean temperature over the full length of their record, with the largest being at Vernadsky (formerly Faraday) (0.46° ± 0.15°C·dec −1 ) on the western side of the Antarctic Peninsula. The deepening of the Amundsen Sea low as a result of the more positive SAM and changes in the IPO and PDO have contributed to the warming of the Peninsula. Beyond the Antarctic Peninsula there has been little significant change in temperature. The two plateau stations had a small cooling from the late 1970s to the late 1990s consistent with the SAM becoming positive, but have subsequently warmed. During spring there has been an Antarctic‐wide warming, with all but one station having experienced an increase in temperature, although the only trends that were significant were at Vostok, Scott base, Vernadsky and Amundsen‐Scott. In this season, much of the Peninsula/West Antarctic warming can be attributed to tropical Pacific forcing through the IPO/PDO. Abstract : Over recent decades, temperatures across the Antarctic continent have exhibited a complex picture of change with a marked warming of the Antarctic Peninsula but with little overall change elsewhere. The ozone hole has contributed significantly to the warming of the Peninsula, although tropical Pacific climate variability has also played a part. The largest seasonal Antarctic‐wide change has been a warming during the spring, with much of this attributable to tropical variability.